About the Gonfalone of the City of L’Aquila, or for an Hypothesis on the Use of Camera Obscura in XVI Century (diségno, 2023)
The representation of the city of L'Aquila, in the banner, the so called Gonfalone, painted in 1579 by Giovan Paolo Cardone, is the oldest known view of the historic center. Contrary to what usually occurs in devotional representations, mostly symbolic, the banner gives a surprisingly detailed image, where the numerous elements still recognizable today appear strongly corresponding. The mountainous nature of the territory, even close to the city, allow to have points of view from above of the urban center that offer sights similar to the one represented. The contribution, based on the reconstruction of the historical and cultural context, as well as through a detailed analysis of the artifact and the critical comparison with the current panorama, proposes that a camera obscura has been used to realize the view depicted in the Gonfalone.
Keywords: camera obscura; Gonfalone; points of view; perspective; photography